2013
DOI: 10.4103/0970-4388.112394
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the bleaching efficacy of three different agents used for intracoronal bleaching of discolored primary teeth: An in vitro study

Abstract: The bleaching efficacy of 10% hydrogen peroxide gel was more effective than 10% carbamide peroxide and sodium perborate in bleaching the artificially discolored primary teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
1
9
0
3
Order By: Relevance
“…2 The previous studies showed that sodium perborate was able to bleach nonvital teeth. [17][18][19] All groups in the present study included sodium perborate in order to compare the efficacy of two laser systems. Ganesh et al used a control group in which bleaching was done with distilled water, and reported no significant changes after 14 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The previous studies showed that sodium perborate was able to bleach nonvital teeth. [17][18][19] All groups in the present study included sodium perborate in order to compare the efficacy of two laser systems. Ganesh et al used a control group in which bleaching was done with distilled water, and reported no significant changes after 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Ganesh et al used a control group in which bleaching was done with distilled water, and reported no significant changes after 14 days. 19 The no laser group was accepted as the control group in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, one additional in vitro study [ 115 ] was focused on an exploration of the tooth-bleaching efficacies of a 10% ( w/w ) H 2 O 2 gel, 10% ( w/w ) CP and a 2.0 g quantity of peroxoborate towards human primary maxillary central incisors which were discolored with freshly collected human blood. From the results acquired, it was concluded that all the bleaching agents applied were effective at 7- and 14-day post-treatment time-points ( p = 0.013), and that the 10% ( w/w ) H 2 O 2 gel treatment exerted a greater tooth-whitening activity than those of the 10% ( w/w ) CP and peroxoborate formulations applied.…”
Section: Peroxoborate Species As Alternative Tooth-whitening Agentmentioning
confidence: 99%
“…Estos parámetros resultaron en un tamaño mínimo muestral de 11 unidades por grupo incluyendo una proporción de pérdida del 10 %. Este es consistente con el tamaño muestral grupal observado en otros trabajos clínicos de blanqueamiento con metodología similar; Lim et al (2004), que utilizaron un n=11, y Ganesh et al (2013), que utilizó un n=10. Debido a una exitosa recolección de dientes, se utilizó finalmente un n=22 para cada grupo de estudio.…”
Section: Materials Y Métodounclassified